1997
DOI: 10.1016/s0925-4773(97)00110-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Brx1 (Rieg gene), Sonic hedgehog, Nkx2.2, Dlx1 and Arx during zona limitans intrathalamica and embryonic ventral lateral geniculate nuclear formation

Abstract: The Brx1 homeobox gene has been isolated and shown to be expressed in the zona limitans intrathalamica (ZLI) of the mouse embryo. Brx1 is a member of the Brx gene family and comprises the genes for Brx1a and Brx1b, which differ in the sequence in the region located on the 5'-terminal side of the homeobox. The complete amino acid sequences of the open reading frame of Brx1a and Brx1b were determined and each was found to be similar to that of Rgs, the mouse homologue of the Rieger syndrome associated human RIEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 44 publications
11
106
0
Order By: Relevance
“…6C, D, F-FЈЈЈ). At E13.5, Zic2/eGFP cells in this stream coincided with a region positive for Arx, a transcription factor that marks the prethalamus and its boundary with the thalamus (Kitamura et al, 1997;Fig. 6B).…”
Section: Dј-eј Dјј-eјј)mentioning
confidence: 95%
See 1 more Smart Citation
“…6C, D, F-FЈЈЈ). At E13.5, Zic2/eGFP cells in this stream coincided with a region positive for Arx, a transcription factor that marks the prethalamus and its boundary with the thalamus (Kitamura et al, 1997;Fig. 6B).…”
Section: Dј-eј Dјј-eјј)mentioning
confidence: 95%
“…Although previous evidence has suggested that a subpopulation of vLGN INs originate in the prethalamic subventricular zone (Kitamura et al, 1997;Vue et al, 2009;Golding et al, 2014), their movement from the neuroepithelium has never been confirmed. To confirm the existence of such cell migration, we first determined, by BrdU uptake experiments, the birthdate of most Zic2 IN at E12.5 (Fig.…”
Section: Dј-eј Dјј-eјј)mentioning
confidence: 96%
“…The fact that Lhx5 is expressed in a mutant without PTh represents a genetic dissection of the rostral-dorsal diencephalon. We analyzed this by colocalizing EMT marker Tbr1 (Puelles et al, 2000) and PTh marker Arx (Kitamura et al, 1997), which show contiguous domains in the rostral-dorsal diencephalon (supplemental Fig. 1 F, available at www.…”
Section: Regional Hypothalamic Patterning In the Shh-c Embryomentioning
confidence: 99%
“…Selective expression of hedgehog family genes in the MDO of vertebrate model organisms is observed in lamprey (Osorio et al, 2005), zebrafish (Macdonald et al, 1995), frog (Ruiz i Altaba, 1998), chick (Kitamura et al, 1997), and mouse (Kitamura et al, 1997). Experimental abrogation of Shh signaling in zebrafish, chick, and mouse results in loss of genetic fate determinants and cell identity in prethalamus and thalamus (Kiecker and Lumsden, 2004;Scholpp et al, 2006;Vue et al, 2009).…”
Section: Patterning Of Developing Thalamus and Hypothalamus By Secretmentioning
confidence: 99%